2003
DOI: 10.1038/nature01861
|View full text |Cite
|
Sign up to set email alerts
|

Action plans used in action observation

Abstract: How do we understand the actions of others? According to the direct matching hypothesis, action understanding results from a mechanism that maps an observed action onto motor representations of that action. Although supported by neurophysiological and brain-imaging studies, direct evidence for this hypothesis is sparse. In visually guided actions, task-specific proactive eye movements are crucial for planning and control. Because the eyes are free to move when observing such actions, the direct matching hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
520
7
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 627 publications
(569 citation statements)
references
References 28 publications
40
520
7
2
Order By: Relevance
“…There is substantial evidence that observers predict actions (Kilner, Vargaa, Duval, Blakemore, & Sirigu, 2004;Ramnani & Miall, 2004;Flanagan & Johansson, 2003;Graf et al, 2007;see Wilson & Knoblich, 2005 for a review). For example, the readiness potential, that indexes the preparation of motor responses, is present from about 500ms prior the observation of a predictable hand action (Kilner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that observers predict actions (Kilner, Vargaa, Duval, Blakemore, & Sirigu, 2004;Ramnani & Miall, 2004;Flanagan & Johansson, 2003;Graf et al, 2007;see Wilson & Knoblich, 2005 for a review). For example, the readiness potential, that indexes the preparation of motor responses, is present from about 500ms prior the observation of a predictable hand action (Kilner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of research suggests that people run internal simulations based on their own motor repertoire when predicting the future course of other people's actions (Blakemore & Frith, 2005;Kilner, Marchant, & Frith, 2009;Wilson & Knoblich, 2005). For instance, eye movements during action observation are predictive (Flanagan & Johansson, 2003;Rotman, Troje, Johansson, & Flanagan, 2006), and motor regions of the brain are engaged when participants must predict upcoming action events (Kilner, Vargas, Duval, Blakemore, & Sirigu, 2004;Stadler et al, 2011). Earlier findings from monkey neurophysiological work revealed activation of mirror neurons within premotor cortex when the monkeys observed the relevant phase of an observed grasping movement being occluded (UmiltĂ  et al, 2001).…”
mentioning
confidence: 99%
“…Humans seem to run internal sensorimotor simulations when predicting the future course of observed actions (see Sebanz & Knoblich, 2009;Wilson & Knoblich, 2005, for reviews). Flanagan and Johansson (2003) showed that eye movements during action observation were predictive rather than reactive, and Kilner, Vargas, Duval, Blakemore, and Sirigu (2004) found that motor-related brain activity occurred prior to observing a predictable movement. Furthermore, increased premotor activation was found when observers predicted the future course of partly invisible action sequences (Stadler et al, in press), indicating that internal simulation is used for action prediction.…”
Section: Introductionmentioning
confidence: 99%